Implementasi UU No.4 Tahun 1997 tentang Penyandang Cacat di Perusahaan Industri di kota Padang (Deskriptif Kualitatif) - Ike Armaretta (Universitas Negeri Padang, 2014)
ABSTRACT: The Implementation of Law Number 4 Year 1997 about People with Special Needs in Industrial Enterprises. Thesis. Undergraduate Program of Faculty of Education of Padang State University This research discussed about the implementation of Law Number 4 Year 1997 about the people with special needs in the workplace. The purpose of this research was to reveal the implementation of the law, the way companies identified the employees, the companies’ efforts to recruit their employees, the way companies hired people with special needs and the obstacles found when the companies hired people with special needs. The law was about government and private enterprises giving opportunities and equal treatment to the people with special needs by hiring them in the companies based on the types and levels of their disabilities, education and ability whose numbers was adjusted to the number of the employees and the companies qualification. This was a descriptive research that used qualitative approach. The data was collected through observation, interview and documentation. The result of the research indicated that the Law Number 4 Year 1997 was not yet implemented as it was organized by the government. In identifying the employees, the companies put higher priority to the applicants’ physical health rather than to their potential or ability. Based on the responses given by the companies, it was concluded that the companies were in doubt or unsure about the potential of the people with special needs although many of them had good achievement in their field, or they had gotten related education and training to the workplace. Kata kunci : Penyandang Cacat Di Perusahaan Industri Kota Padang.